Rapid Oligocene to Early Miocene Extension Along the Grant Range Detachment System, Nevada, USA: Insights From Multipart Cooling Histories of Footwall Rocks. Issue 12 (22nd December 2018) - Long, Sean P.; Heizler, Matthew T.; Thomson, Stuart N.; Reiners, Peter W.; Fryxell, Joan E.
Abstract: In Nevada and Utah, the Cordilleran orogen underwent a protracted Cenozoic transition to an extensional setting. However, the geodynamic processes that controlled this transition are poorly understood, in part because the space‐time patterns of extension are not known in many areas. Localities of pre‐Neogene extension have the potential to elucidate the dynamics of the Cordilleran crust during the final stages of subduction. Here we present data that constrain the timing of extension in the Grant Range in eastern Nevada, which was deformed by a low‐angle normal fault system. We present temperature‐time histories of eight granite samples exhumed by this fault system, constrained by muscovite 40 Ar/ 39 Ar multi‐diffusion domain modeling and fission track and (U‐Th)/He ages from zircon and apatite. These data demonstrate rapid cooling (20–35 °C/Myr) from 350–425 to 25–50 °C between 28–31 and 15–19 Ma. The fault system accommodated 24 km of extension ( 115%), and exhumed the granite samples from 7–9 km depths to the near‐surface. Rapid Oligocene‐early Miocene cooling is interpreted to date the duration of motion on the fault system, and defines an extension rate of 1.5–2.6 km/Myr. This was one of the most significant fault systems active during an episode of spatially distributed late Eocene‐Oligocene extension, which overlaps temporally with volcanism generated by slab rollback. Reduced interplate coupling that accompanied slab rollback is interpreted as the primary driver of extension of the Cordilleran plateau during the final stages of subduction. This supports a scenario of orogenic collapse that proceeded in distinct episodes that were initiated by external geodynamic events. Key Points: The Grant Range detachment system accommodated 24 km of extension (115%) between 31 and 15 Ma and was a significant syn‐rollback fault system Decreased interplate coupling during slab rollback likely drove the earliest episode of distributed extension in the Cordilleran plateau Muscovite 40 Ar/ 39 Ar multi‐diffusion domain modeling is effective for constraining the cooling histories of rocks between 425 and 250 °C